Hypothyroidism-associated angioedema. Issue 2 (2nd April 2020) - Greiner, Benjamin; Pelton, Jameson; Baker, Damon
Abstract: We present a 41-year-old woman with hypothyroidism who presented to the emergency department with acute onset of angioedema and profound hypothyroidism. She required complex airway management and medical treatment before being discharged home 10 days later. This may be the first case of hypothyroidism-induced angioedema that was not associated with chronic urticaria or hives.